166k views
3 votes
9(p-4)= 6p solve for p

2 Answers

2 votes

9(p-4)= 6p

multiply the bracket by 9

(9)(p)=9p

(9)(-4)=-36

9p-36=6p

move +9p to the other side to combine like terms

sign changes from +9p to -9p

9p-9p-36=6p-9p

-36=6p-9p

-36=-3p

divide both sides by -3 to get p by itself

-36/-3=-3p/3

12=p

answer:

p=12

User MajorTom
by
5.3k points
3 votes

Answer:

p = 12

Explanation:

9(p - 4) = 6p

simplify

9p - 36 = 6p

subtract 6p from both sides

3p - 36 = 0

add 36 to both sides

3p = 36

divide both sides by 3

p = 12

User Rahul Sharma
by
5.4k points